The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1128/mcb.16.6.2814
|View full text |Cite
|
Sign up to set email alerts
|

2-Aminopurine Selectively Inhibits Splicing of Tumor Necrosis Factor Alpha mRNA

Abstract: 2-Aminopurine (2-AP) inhibits specific kinases that phosphorylate the ␣ subunit of eukaryotic translation initiation factor 2. One of these, PKR, is also involved in signal transduction. We show here that 2-AP selectively inhibits expression of tumor necrosis factor alpha (TNF-␣) mRNA in primary human lymphoid cells. 2-AP does not inhibit transcription of the human TNF-␣ gene, nor does it affect mRNA stability. Instead, the flow of short-lived precursor transcripts into mature TNF-␣ mRNA is blocked. When 2-AP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 56 publications
5
62
0
Order By: Relevance
“…2AP blocks the splicing of pre-mRNA transcripts. But, as shown previously, TNF-␣ pre-mRNA transcripts are unstable (11). As Be stimulation continues to drive the synthesis of pre-mRNA transcripts, we observed a slight increase in the levels relative to the profound decrease in levels in the presence of PTX.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…2AP blocks the splicing of pre-mRNA transcripts. But, as shown previously, TNF-␣ pre-mRNA transcripts are unstable (11). As Be stimulation continues to drive the synthesis of pre-mRNA transcripts, we observed a slight increase in the levels relative to the profound decrease in levels in the presence of PTX.…”
Section: Discussionsupporting
confidence: 47%
“…Our previous studies show that the percentage of Be-specific CD4 ϩ T cells are found in the range of 1.4-29% in CBD BAL cells (2). Be-induced TNF-␣ pre-mRNA upregulation was inhibited by PTX, a transcription inhibitor (12,13), and the splicing of TNF-␣ pre-mRNA into mature mRNA transcripts was inhibited by 2AP, a splicing inhibitor (11). In addition, the data indicate that this Be-induced TNF-␣ production was associated with Be-specific upregulation of AP-1 and NF-B transcription factors in the nuclei of CBD BAL cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations